Comparative catalytic activity of Mn(Salen) complexes grafted on SBA-15 functionalized with amine, thiol and sulfonic acid groups for selective aerial oxidation of limonene - Salkia, Lakshi; Srinivas, Darbha; Ratnasamy, Paul (Microporous and Mesoporous Materials, 2007)
SBA-15 molecular sieves were functionalized with propylamine, propylthiol and propylsulfonic acid groups. Mn(Salen)Cl complexes were grafted on these organo-functionalized SBA-15. The support and the type of organo-functional group influenced the electronic structure (oxidation state and redox behavior) and chemo selectivity of the Mn-complexes in the oxidation of limonene. The Mn ions were reduced from +3 to +2, the extent of this reduction on different supports decreasing in the order: SBA- 15-pr-SH > SBA- 15-prSO(3)H > SBA-15-pr-NH2- Mn(Salen)Cl supported on propylthiol-functionalized SBA-15 yielded the 1,2-limonene epoxide with 100% chemo- and regioselectivity. Higher electron density at the site of Mn ions and the consequent lower redox potential of the Mn-complexes on immobilization are the probable causes for their efficient and selective catalytic activity. Solvents, additives (N-MeIm) and co-reagents (iso-butyraldehyde), which facilitated formation of Mn2+ ions, enhance the catalytic activity. A part of the Mn complexes was leached out of the solid phase during the reaction and the extent of this with different catalysts decreased in the order: SBA-l5-pr-NH2-Mn(Salen)Cl > SBA- 15-pr-SO3H-Mn(Salen)Cl > SBA- 15-pr-SH-Mn(Salen)Cl. (C) 2007 Elsevier Inc. All rights reserved

Challenges and opportunities in biofuels production - Srinivas, Darbha; Satyarthi, Jitendra Kumar (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2012)
Biofuels are attractive alternative to petroleum diesel. They are renewable, non-toxic, biodegradable, carbon neutral and lead to reduced tailpipe emissions. This article presents the current state-of-art processes of their production and discusses the opportunities and future challenges in this area of research.
Keywords: Biodiesel; biofuels; Deoxygenation; Hydrotreatment; Renewable fuels; Solid catalysts; Transesterification (fatty acid glycerides); Vegetable oils/fats

Catalytic activity of ZIF-8 in the synthesis of styrene carbonate from CO2 and styrene oxide - Zhu, Minqi; Srinivas, Darbha; Bhogeswararao, Seemala; Ratnasamy, Paul; Carreon, Moises A. (Catalysis Communications, 2013)
The catalytic activity of ZIF-8 in the synthesis of styrene carbonate from carbon dioxide and styrene oxide is presented. ZIF-8 crystals displayed catalytic activity even at temperatures as low as 50 degrees C, with styrene carbonate yields as high as similar to 54% at 100 degrees C. In contrast to many prior-art catalysts, solvents or co-catalysts were not required. Pyridine and ammonia were used as probe molecules to estimate the type and density of acid sites in fresh and reused ZIF-8 catalysts. DRIFT spectroscopy of adsorbed pyridine revealed the presence of both Bronsted (B) and Lewis (L) acid sites. The B-sites have nearly vanished in the case of recycled ZIF-8 catalysts. The simultaneous presence of both the acid sites and the nitrogen basic moieties from the imidazole linker in ZIF-8 promoted the adsorption of the CO2 on the solid surface and its further conversion to the cyclic carbonate. The ZIF-8 catalysts could be recycled and reused without significant loss in catalytic activity. Published by Elsevier B.V.
Keywords: CO2 conversion; cyclic carbonates; Styrene carbonate; Zeolitic imidazolate frameworks; ZIF-8

Cu(II) conjugation along the transformation of a vitamin K-3 derivative to a dinaphthoquinone methide radical - Badave, Kirti D.; Patil, Shalaka S.; Khan, Ayesha A.; Srinivas, Darbha; Butcher, Raymond J.; Gonnade, Rajesh G.; Puranik, Vedavati G.; Pinjari, Rahul V.; Gejji, Shridhar P.; Rane, Sandhya Y. (New Journal of Chemistry, 2014)
1,1'-Methide-bi-vitamin K-3 (B) has been isolated as a dinaphthoquinone methide radical (DNQM) by the transformation of 1-imino(acetylhydrazino)-vitamin K-3 (A). The transformation follows a biomimetic activation pathway mediated via Cu(II) ion catalyzed oxidative coupling. Single crystal X-ray and electron spin resonance (ESR) experiments combined with density functional calculations elucidate the ``resonance structure'' of the DNQM radical (B). Fluorescence investigations reveal that DNQM facilitates interaction with the cysteine residue. As compared to the parent substrate, B shows a depletion in the level of GSH, triggering apoptosis in HeLa cells.